2019
DOI: 10.1016/j.heliyon.2019.e01421
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical survey of medicinal plants used for diabetes treatment in Rabat, Morocco

Abstract: Diabetes mellitus is a major public health problem in Morocco. The value of ethnobotanical information is now increasingly acknowledged. To inventory and to provide ethnobotanical information on some of the medicinal plants used in traditional medicine to treat diabetes in Rabat (Morocco), a survey was undertaken from March 1 st to April 30 th 2018. This survey was conducted using a semi-structured questionnaire targeting diabetic patients from the SOS Diabetes Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
73
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 56 publications
14
73
1
4
Order By: Relevance
“…Lamiaceae and Leguminosae were the most commonly reported plant families. Interview results showed that the most frequently used plants were Trigonella foenumgraecum, Salvia officinalis and Olea europaea [25].…”
Section: Ethnobotanical Studiesmentioning
confidence: 99%
“…Lamiaceae and Leguminosae were the most commonly reported plant families. Interview results showed that the most frequently used plants were Trigonella foenumgraecum, Salvia officinalis and Olea europaea [25].…”
Section: Ethnobotanical Studiesmentioning
confidence: 99%
“…24 The widespread use of leaves for treatment of diabetes mellitus has also been reported in Pakhtunkhwa (Pakistan) and Rabat (Morocco). 24,25 Also, leaves were identified as the most commonly used organ of antidiabetic plants elsewhere in Indonesia. 26 As commonly practiced nationwide, people of Baturraden and Sumbang also recognized three methods in preparing their water extract of herbal preparations, and they were tea, infusion, and decoction.…”
Section: Discussionmentioning
confidence: 99%
“…Curcuminoids are compounds contained in turmeric (Curcuma longa), a plant whose rhizome is used in Morocco for its medicinal properties and culinary purposes (Bellakhdar, 1997;Skalli et al, 2019).…”
Section: Curcuminoidsmentioning
confidence: 99%
“…Here we will focus on the immunomodulatory activity of four medicinal plants widely used in traditional medicine in Morocco (Bellakhdar, 1997;Skalli et al, 2019): garlic (Allium sativum), Ginger (Zingiber of icinale), licorice (Glycyrrhiza glabra) and black pepper (Piper nigrum).…”
Section: Indirect Action On Sars-cov-2 By An Immunomodulatory Effectmentioning
confidence: 99%